The Formulation of Binding Agent Concentration on Raw Restructured Goat Meat Trimming Product (Jurnal Ilmu dan Teknologi Hasil Ternak, 2008)
The utilization of raw materials and formulation method would affect the quality of the processed meat product. Therefore, a research on the processing method to produce a raw structured product should be conducted. The research was testing a single factor comprises of following parameters: control (without) binding agent; 0.3%, 0.5% and 0.7% sodium alginat and 0.3%, 0.5% and 0.7% carragenan, respectively. The results showed that the goat meat trimming could be used as raw materials in the production of the best restructured meat using 0.5% carragenan. This raw restructured meat produced had a loss weight of 1.67%, pH value  7.89, WHC  48.345, and moisture content  75.20%.   Keywords : sodium alginat, carragenan, raw restructured goat meat trimming.